Association of circulating preptin with non-alcoholic fatty liver disease: A case-control study - Arğun, Derya; Basim, Pelin; Börkü Uysal, Betül; Argun, Ferit (Journal of Surgery and Medicine, 2021)
Background/Aim: Non-alcoholic fatty liver disease (NAFLD) is the hepatic component of metabolic disorders and identifying patients with a high risk of fibrosis is crucial. A scoring system, the FIB-4 score, based on clinical and biochemical parameters was developed to predict fibrosis. NAFLD is associated with various peptide hormones. However, the relationship of preptin, a newly discovered peptide critical for regulating energy metabolism, with NAFLD remains unclear. Therefore, we aimed to determine the relationship of preptin with NAFLD and evaluate whether there was an association between serum preptin levels and FIB-4 score. Methods: In this prospective study, serum biochemical parameters and serum preptin levels of 51 patients with grade 2-3 hepatosteatosis proven by ultrasonography and 35 healthy controls with similar demographic characteristics were compared. Serum preptin levels were measured using ELISA. The FIB-4 scores were calculated and recorded. Results: The serum preptin levels were higher in the NAFLD group than in the control cases (P<0.001). Among the patients, the sensitivity, specificity, positive predictive, and negative predictive values of preptin above a cut-off value of ≥62.3 were 85.7%, 56.9%, 85.3%, and 57.7%, respectively, with an accuracy of 68.6%. The preptin level was negatively correlated with the FIB-4 score and AST in the patient group (P=0.004 and P=0.014, respectively). The linear regression model revealed that there was a significant relationship between the FIB-4 score and preptin (P<0.05). Each 1 unit increase in the FIB-4 score induced a decrease of 86.37 units in preptin values (R²=%8.5). Conclusion: We demonstrated that the serum preptin levels were higher in patients with NAFLD than healthy individuals and negatively correlated with the FIB-4 score and AST levels. Preptin may have a role in the pathogenesis of NAFLD, is likely to distinguish patients with mild and severe liver damage and may be a useful marker in predicting a high risk for progression to fibrosis. Further studies establishing a stratification system including plasma preptin level and the FIB-4 score and its verification with liver biopsies are required.